证明(sinα+cosα-1)(sinα-cosα+1)分之2sinαcosα=sinα分之1+cosα

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 22:03:28
证明(sinα+cosα-1)(sinα-cosα+1)分之2sinαcosα=sinα分之1+cosα证明(sinα+cosα-1)(sinα-cosα+1)分之2sinαcosα=sinα分之1+

证明(sinα+cosα-1)(sinα-cosα+1)分之2sinαcosα=sinα分之1+cosα
证明(sinα+cosα-1)(sinα-cosα+1)分之2sinαcosα=sinα分之1+cosα

证明(sinα+cosα-1)(sinα-cosα+1)分之2sinαcosα=sinα分之1+cosα
(sinα+cosα-1)(sinα-cosα+1)分之2sinαcosα
=2sinacosa/[sina+(cosa-1)][sina-(cosa-1)]
=2sinacosa/[sin²a-cos²a+2cosa-1)
=2sinacosa/(2cosa-2cos²a)
=sina/(1-cosa)
=sina(1+cosa)/(1-cos²a)
=sina(1+cosa)/sin²a
=(1+cosa)/sina